Effects of respiratory muscle training on respiratory function and functional outcomes in patients with myasthenia gravis: a systematic review - Bi, Zi-Ting; Xiao, Jing-Hua; Wei, Jing-Xue; Huang, Lang; Li, Ying-Dong; Zhang, Yue-Mi; Huang, Jian; Luo, Chao-Song; Zhang, Jia-Mei; Zhang, Yun-Shan (Frontiers in Neurology, 2025)
BackgroundRespiratory muscle training is a structured intervention designed to enhance respiratory muscle function, but robust evidence on its effects in myasthenia gravis remains limited. This systematic review evaluates the impact of respiratory muscle training on respiratory function and functional outcomes in patients with myasthenia gravis.MethodsA comprehensive search of six databases was conducted without date restrictions until May 1, 2025, to identify studies meeting inclusion criteria: (1) myasthenia gravis patients aged ≥18 years, (2) respiratory muscle training involving inspiratory and expiratory muscle training, (3) outcomes on respiratory muscle strength, respiratory muscle endurance, pulmonary function tests, and functional outcome, (4) study designs like randomised controlled trials (RCTs), cohort studies, case–control trials, and quasi-experimental studies. Two reviewers independently screened studies, extracted data, and assessed methodological quality and evidence level using appropriate tools. Due to limited RCTs and heterogeneity in participants, interventions, and outcomes, a descriptive synthesis was performed.ResultsSeven studies involving 223 participants (99 males and 124 females) with a mean age of 57.5 years were systematically reviewed, including two RCTs, one quasi-controlled study, one case–control study, and three cohort studies, all of which demonstrated moderate-to-high methodological quality (evidence levels 2–4). Respiratory muscle training programs involved inspiratory-expiratory training and inspiratory-only training, with parameters varying widely: intensity ranged from 15 to 75% of maximal respiratory pressures or 50 to 60% of maximal voluntary ventilation, frequency spanned from 3 to 10 sessions weekly, sessions lasted 10 to 30 min, and total intervention periods extended from 4 weeks to 12 months. Devices included threshold and variable resistance trainers, all applied under supervised conditions alongside conventional myasthenia gravis medications. All five studies evaluating respiratory muscle endurance and functional outcomes reported statistically significant enhancements (p < 0.05). Respiratory muscle strength and pulmonary function results were inconsistent. Maximal inspiratory pressure improved significantly in two of six studies (p < 0.01), while maximal expiratory pressure improved in two of three studies (p < 0.05). Among six studies measuring forced expiratory volume in 1 s, three measuring forced vital capacity, and three measuring peak expiratory flow, only two studies reported significant improvements in forced expiratory volume in 1 s and forced vital capacity (p < 0.05), while others found no effects. Adverse events reported in three studies were attributed to comorbidities rather than interventions.ConclusionRespiratory muscle training can enhance respiratory muscle endurance and functional outcomes in patients with myasthenia gravis. However, evidence regarding its effects on respiratory muscle strength and pulmonary function remains inconsistent and is constrained by methodological limitations. Higher-quality trials are warranted to validate these findings and optimize intervention protocols.Systematic review registrationCRD42024516112.